2023
DOI: 10.3390/biomedicines11041103
|View full text |Cite
|
Sign up to set email alerts
|

The DASciS Software for BSI Calculation as a Valuable Prognostic Tool in mCRPC Treated with 223RaCl2: A Multicenter Italian Study

Abstract: Background/Aim: Radium-223 dichloride (223RaCl2) represents a therapeutic option for metastatic castration-resistant prostate cancer (mCRPC) patients dealing with symptomatic bone metastases. The identification of baseline variables potentially affecting the life-prolonging role of 223RaCl2 is still ongoing. Bone scan index (BSI) defines the total load of bone metastatic disease detected on a bone scan (BS) and is expressed as a percentage value of the whole bone mass. The aim of this multicenter study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A single-center study found that aBSI calculation derived using the DASciS software package, developed by the Sapienza University of Rome, is useful for predicting survival in mCRPC candidates treated with Ra-223 [11], which was also shown by the results of a multicenter study conducted in Italy [30]. This package has been demonstrated to be a simple tool that requires no more than a single demonstrative training session for a participating center.…”
Section: Discussionmentioning
confidence: 87%
“…A single-center study found that aBSI calculation derived using the DASciS software package, developed by the Sapienza University of Rome, is useful for predicting survival in mCRPC candidates treated with Ra-223 [11], which was also shown by the results of a multicenter study conducted in Italy [30]. This package has been demonstrated to be a simple tool that requires no more than a single demonstrative training session for a participating center.…”
Section: Discussionmentioning
confidence: 87%